Outcome of SARS-CoV-2 infection among patients with common variable immunodeficiency and a matched control group: A Danish nationwide cohort study - Katzenstein, Terese L.; Rasmussen, Line D.; Drabe, Camilla Helberg; Larsen, Carsten Schade; Hansen, Ann-Brit Eg; Stærkind, Mette; Knudsen, Lene Surland; Hansen, Christian Holm; Obel, Niels (Frontiers in Immunology, 2022)
The risk of Severe Adult Respiratory Coronavirus-2 (SARS-CoV-2) infection and the course of the infection among individuals with common variable immunodeficiency (CVID) relative to the general population has been a matter of debate. We conducted a Danish nationwide study comparing the timing of SARS-CoV-2 vaccination, the risk of first confirmed SARS-CoV-2 infection, re-infection as well as the outcome of infection among individuals with CVID relative to an age- and gender matched control group. Cox-regression was used to calculate incidence rate ratios. The CVID patients received SARS-CoV-2 vaccinations earlier than those included in the population control group. Even so the risks of both first infection and re-infection were increased among the individuals with CVID. The CVID group also had increased risk for hospital contacts due to SARS-CoV-2 infection relative to the general population. However, reassuringly, the risk of mechanical ventilation and death did not differ between the groups, but the numbers were low in both groups, making the estimates uncertain. Though this is the largest study investigating the risk of SARS-CoV-2 infections and outcomes hereof among individuals with CVID relative to the general population, we cannot rule out minor differences in severity, which might only be detectable with an even larger sample size.